PELAKSANAAN SITA JAMINAN DALAM HUKUM ACARA ARBITRASE - Sujayadi Sujayadi; Yuniarti Yuniarti (Yuridika, 2010)
Alternative dispute resolution (ADR) includes dispute resolution processes and techniques that act as a means for disagreeing parties to come to an agreement short of litigation. Despite historic resistance to ADR by many popular parties and their advocates, some courts now require some parties to resort to ADR of some type, usually mediation. The rising popularity of ADR can be explained by the increasing caseload of traditional courts, the perception that ADR imposes fewer costs than litigation, a preference for confidentiality, and the desire of some parties to have greater control over the selection of the individual or individuals who will decide their dispute. In Indonesia based on the Law No. 30/1999 concerning Alternative Dispute Resolution and Arbitration, ADR is interpreted as alternative to adjudication as it is reflected in the title of the Law No. 30/1999. Based on article 32 the collateral forclosure is enable to be done. The procedure of this were adopting the procedure of the collateral forclosure in civil court.